Burma Boy - Bandele, Biyi (Kachifo Ltd, 2007)
It's winter 1944 and the Second World War is entering its most crucial stage. A few month ago Ali Banana was apprenticed to a whip-wielding blacksmith in his rural hometown; now he's behind enemy lines, trekking through the Burmese jungle, a private in Thunder Brigade. He is fourteen years old. Led by the scarred, charismatic Sergent Damisa, the unit has been given orders to go behind enemy lines and wreck havoc. But the jungle is a treacherous place, riddled with Japanese snipers, ambush, infection and disease. As torrential rain turn the landscape into a mud riven death trap, the losses mount up. Exhausted and far from home, the men of D-Section Thunder Brigade are besieged yet indomitable...
Keywords: Fiction